Total phenolic content and antioxidant activity of Orthosiphon stamineus and Andrographis paniculata / Siti Latifah Abdullah - Abdullah, Siti Latifah (Faculty of Applied Sciences, 2010)
The total phenolic content and antioxidant activity of Orthosiphon stamineus and Andrographis paniculata leaves were investigated. The total phenolic content was evaluated using Folin-Ciocalteu reagent and antioxidant activity was evaluated by measuring free radical scavenging activity by 2,2-diphenyl-l- picryhydrazyl (DPPH). The crude extracted from Andrographis paniculata leaves has higher amount of phenolic content (2.1708 mgGAE/g sample) than Orthosiphon stamineus crude extract (1.8884 mgGAE/g sample). The crude leaves extracted from Orthosiphon stamineus displayed the higher percentage of scavenging activities than Andrographis paniculata crude extract